Landscape conservation as a strategy for recovering biodiversity: Lessons from a long‐term program of pasture restoration in the southern Atlantic Forest. Issue 9 (25th July 2022) - Cardoso, Fernanda C. G.; Capellesso, Elivane S.; de Britez, Ricardo Miranda; Inague, Gabriel; Marques, Marcia C. M.
Abstract: Although ecological restoration has entered the global agenda to reverse different anthropogenic disturbances, we still know little about how this solution interacts with other conservation strategies, to avoid the progressive loss of species and ecosystem services. Here we evaluate one of the pioneering restoration programs in the southern Brazilian Atlantic Forest, where the combination of conservation and restoration efforts has been carried out for 20 years. Specifically, we tested how landscape characteristics, restoration strategies and environmental characteristics affect the results of the restoration of pastures. We established 65 circular plots (total 4.0 ha) along restoration areas (3–10 years) and sampled trees and shrubs composing the canopy (DBH ≥ 5 cm) and understorey (DBH < 5 cm, height > 1.3 m). We analysed the landscape metrics (proportion of old‐growth forests in 200, 500 and 1, 000 m buffers around each plot; and area and distance of the nearest‐neighbouring old‐growth forests). We explored the multiple effects of landscape, restoration strategy (reforestation, natural regeneration) and environmental variables (soil, pasture grass types) on the species composition and multiple diversity metrics of restoration areas. The species composition was very similar among restoration ages and restoration strategies. We found positive and strong effects of old‐growth forest (200 m buffer) proportion on the species richness and Shannon diversity (canopy and understorey), above‐ground biomass (canopy) and functional diversity (understorey) of restoration areas. The restoration strategies affected forest structure, and, in general, the reforestation strategy increased above‐ground biomass, Shannon, functional and phylogenetic diversities (in canopy), and percentage of endemic species and biomass (understorey), when compared to natural regeneration. The 20‐year experience in the southern Atlantic Forest showed that programs focused on landscape conservation associated with a mixture of restoration strategies (i.e. natural regeneration in larger areas and active restoration in more disturbed sites), can be an efficient strategy to ensure biodiversity and ecosystem services in tropical landscapes. Synthesis and applications . To manage degraded tropical lands and achieve global targets for biodiversity and ecosystem services, it is necessary to first ensure the conservation of natural remnants and then use multiple restoration strategies in less resilient areas. Abstract : To manage degraded tropical lands and achieve global targets for biodiversity and ecosystem services, it is necessary to first ensure the conservation of natural remnants and then use multiple restoration strategies in less resilient areas. Resumo: Embora a restauração ecológica tenha entrado na agenda ambiental global para reverter diferentes distúrbios antropogênicos, ainda sabemos pouco sobre como essa ação interage com outras estratégias de conservação, para evitar a perda progressiva de espécies e serviços ecossistêmicos. Neste estudo avaliamos um dos programas pioneiros de restauração na Mata Atlântica do sul do Brasil, onde esforços para conservação e restauração são realizados há 20 anos. Especificamente, testamos como as características da paisagem, estratégias de restauração e características do ambiente afetam os resultados da restauração de pastagens. Estabelecemos 65 parcelas circulares (total de 4 ha) ao longo de áreas de restauração (3–10 anos) e amostramos árvores e arbustos que compõem o dossel (DAP > 5 cm) e sub‐bosque (DAP <  5 cm, altura > 1, 3 m). Analisamos as métricas da paisagem (proporção de florestas primárias em um raio de 200, 500 e 1000 m ao redor de cada parcela; e área e distância das florestas primárias vizinhas mais próximas). Nós exploramos os múltiplos efeitos da paisagem, estratégias de restauração (reflorestamento, regeneração natural) e variáveis ambientais (solo, tipos de pastagens) sobre a composição de espécies e múltiplas métricas de diversidade das áreas em restauração. A composição de espécies foi muito semelhante, mesmo entreáreas com idades e estratégias de restauração distintas. Encontramos efeitos positivos e fortes da proporção de floresta primária (no raio de 200 m) sobre a riqueza de espécies e diversidade de Shannon (no dossel e sub‐bosque), biomassa acima do solo (dossel) e diversidade funcional (sub‐bosque) das áreas de restauração. As estratégias de restauração afetaram a estrutura da floresta e, em geral, a estratégia de reflorestamento aumentou a biomassa acima do solo, as diversidades de Shannon, funcionais e filogenéticas (no dossel) e porcentagem de espécies endêmicas e biomassa (sub‐bosque), quando comparada à regeneração natural. A experiência de 20 anos no sul da Mata Atlântica mostrou que programas focados na conservação da paisagem associados a uma mistura de estratégias de restauração (ou seja, regeneração natural em áreas mais amplas e restauração ativa em locais mais perturbados) podem ser uma estratégia eficiente para garantir a biodiversidade e serviços ecossistêmicos em paisagens tropicais. Síntese e aplicações . Para manejar áreas tropicais degradadas e atingir as metas globais de biodiversidade e serviços ecossistêmicos, é necessário primeiro garantir a conservação dos remanescentes naturais e depois usar múltiplas estratégias de restauração em áreas menos resilientes.